Comparison of the Performance of Different Microbial Source Tracking Markers among European and North African Regions. Issue 4 (1st July 2017) - Yahya, Mariem; Blanch, Anicet R.; Meijer, Wim G.; Antoniou, Katerina; Hmaied, Fatma; Ballesté, Elisenda
Abstract : Microbial source tracking (MST) has been extensively used to detect the sources of fecal pollution in water. The inclusion of MST in water management strategies improves the ecological status of the ecosystem and human and animal health under interdisciplinary analysis in all aspects of health care for humans, animals, and the environment (One Health approach). In this study, the performance of MST markers targeting host‐specific Bacteroidales (HF183 and Rum‐2‐Bac) and Bifidobacterium species (HMBif and CWBif) were evaluated in raw sewage collected from human, ruminant, swine, and poultry sources in Tunisia, Cyprus, Ireland, and Spain. In addition, the ratio between somatic coliphages and bacteriophages infecting Bacteroides GA17 (SOMCPH/GA17PH) was measured in Tunisia and Spain. The obtained results showed variability of the bacterial markers between the four countries, suggesting that their usefulness could be affected by several conditions (dietary habits, agricultural practices, and climatic conditions) that differ between countries. The Rum‐2‐Bac marker stood out as a valid MST tool, particularly in Ireland, whereas CWBif was the best option in Tunisia, Spain, and Cyprus. The human‐specific HMBif marker showed good sensitivity and specificity in Tunisia, Spain, and Ireland, whereas HF183 showed a low specificity. However, HF183 was suggested as a good human marker in Ireland and Cyprus because of its higher concentration than HMBif. Regarding viral markers, the ratio of SOMCPH/GA17PH showed a clear discrimination between human and nonhuman samples. The combined use of molecular bacterial markers and the ratio of SOMCPH/GA17PH may improve the success of MST. Core Ideas: Differences among geographical areas have been observed for human source tracking markers Agricultural practices and/or climate conditions may affect the selection of ruminant MST markers. The MST markers described must be validated in each area before use for water management.